Restricted and Repetitive Behaviour in Persons with Autism (Ages 0-18): An Integrative Review of Treatment Related to Occupational Therapy - Patriquin, Melissa; MacKenzie, Diane; Versnel, Joan (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Objective: To identify evidence-based behavioural interventions used to decrease restricted and repetitive behaviour (RRB) in children with autism (ages 0-18); to understand the application of these strategies within the PEO (Person, Environment, Occupation) Model of Occupational Performance and the role of the occupational therapist in addressing this limitation. Background: RRB is a core feature of autism that often impedes functional behaviour. Decreasing RRB to enable functional behaviours is central to the occupational therapist’s role with this population. Many interventions identified as effective for this impairment are based on the principles of applied behaviour analysis (ABA). Method: An integrative review of the literature was completed to identify interventions targeting RRBs. Those found to be effective are described within an ABA framework and within the PEO Model of Occupational Performance. Results: This review identified twenty-eight effective interventions used to treat RRBs in autism relevant to the field of occupational therapy. Categorization of interventions using an ABA framework and the PEO Model allowed comparison between approaches and application to occupational therapy practice. Conclusion: A functional behaviour approach (FBA) used in combination with the PEO model will enable greater understanding of RRBs and provide a more comprehensive approach to the treatment of RRBs in children with autism.